Ensino-avaliação-aprendizagem de multiplicação nos anos iniciais com o uso de tarefas. - BRAGA, Vânia Ferreira (Universidade Federal do Pará, 2025)
This research aimed to investigate, based on a given teaching proposal, how learning occurs in a common classroom context. The processes experienced by students in learning concepts that include the ideas of multiplication were considered in greater depth, rather than just the results of the answers to the tasks. The theoretical framework that guides this study is the debates regarding assessment for learning and the diversification of tasks in the multiplicative field, especially the multiplication operation. The tasks were developed in a school in the municipal education network of Canaã dos Carajás-PA, in a 5th grade class with 32 participants. The investigative path was of a qualitative nature. The data were obtained through oral and written records, produced by groups of students at the time of the development of 6 (six) tasks of the problem, exercise, investigation and exploration type of the multiplicative conceptual field. These tasks were based on the skills proposed by the National Common Curricular Base (BNCC) aimed at the 4th grade of Elementary School, potentially, with the purpose of teaching, learning and evaluation. In developing the activities, we sought to establish connections between additive and multiplicative procedures, numerical regularities of multiples and the processes involved in solving the multiplication algorithm. Data analysis was interpretative of the records obtained in the development of tasks, considered as teaching-learning-evaluation, carried out in the classroom by groups of students. We took as reference the evaluation in the formative perspective (Fernandes, 2005, 2006, 2008), the diversification of tasks, such as exercises, problems, investigation and exploration (Ponte, 2005, 2006, 2010, 2014) and the Theory of Conceptual Fields (Vergnaud, 1993, 1996, 2003, 2009). The diversification of tasks proved to be conducive to understanding and developing strategic schemes for solving situations that involve the four ideas inherent to multiplication. Thus, we indicate the tasks as a way to articulate teaching learning-evaluation, since they were configured as essential elements in a collaborative learning environment, through targeted feedback, for the development of multiplicative thinking. This research showed that investigative/exploratory tasks are still rarely proposed in the classroom context and the fact of recording the paths that were taken to reach the solution was considered somewhat difficult by the students, since this is not a common practice in the classroom. In addition to these results, the research generated o Educational Product: Multiplication teaching-learning-assessment tasks: a proposal for teachers who teach mathematics, which is intended at teachers who teach mathematics with the objective of guiding and supporting these teachers in their classes and, thus, contributing to the teaching learning-evaluation process.